Effective gene flow patterns across a fragmented landscape in southern Costa Rica for Symphonia globulifera (Clusiaceae); a species with mobile seed and pollen dispersers - Solís Hernández, Wendy (2019)
In tropical trees, forest fragmentation has been shown to affect mating and gene flow patterns. Mobile dispersal vectors should be less sensitive to fragmented landscapes and may ameliorate the genetic effects of forest fragmentation on plant populations. To test this hypothesis, we analyzed gene flow patterns in Symphonia globulifera, a tropical tree species with highly mobile pollinators and seed dispersers in the Osa Peninsula in southern Costa Rica. We used microsatellites to study genetic diversity and realized gene flow patterns between a continuous forest and a forest fragment. We found high levels of genetic diversity in adults and seedlings at both sites. Parentage analyses suggest near-neighbor matings and frequent long-distance gene flow events. Half the progeny beneath an adult was not sired by that tree and the majority of established seedlings were the result of long-distance gene dispersal. Gene flow from the forest into the fragment was more common than from the fragment into the continuous forests. Despite long distance gene flow events, seedling spatial genetic structure was stronger and extended further in the forest fragment likely due to limited seed dispersal. We conclude that fragmentation affects gene flow in this tropical tree and may compromise its genetic diversity in forest fragments even for a species with mobile pollen and seed vectors.